FAKTOR RESIKO PREEKLAMSIA PADA IBU HAMIL: LITERATURE REVIEW: FAKTOR RESIKO PREEKLAMSIA PADA IBU HAMIL: LITERATURE REVIEW - Stianto, Mitayakuna; Fatimah, Siti; fitriana, Alfira (LPPM STIKes Bahrul Ulum Jombang, 2022)
Background: The maternal mortality rate in Indonesia in 2020 reached 462 per 100,000 live births. Preeclampsia is some specific symptoms that only appear during pregnancy at 20 weeks of gestation (except for trophoblastic problems), these symptoms include hypertension accompanied by the presence of protein in the urine. The impact of preeclampsia on pregnant women can cause a decrease in consciousness, if preeclampsia is severe it can be accompanied by seizures. The purpose of this study is to determine the risk factors that influence the occurrence of preeclampsia. Subjects and Methods: This was a literature reviews study. The articles used were obtained from PubMed, and Google Scholar. Several passwords were used: